Zastosowanie modeli różnic indywidualnych do wyznaczania kryteriów ocen preferencji - Zaborski, Artur (The Application of the Individual Differences Models for Calculate Preference Judgements, 2007)
The article presents the results of the research leading to comparison of perceptual maps received on the basis of the opinion given by various respondents' groups with simultaneous indication of their individual differences in preference judgements. For making analysis the model PINDIS was used, which is one of the individual differences models based on the assumption that everybody making their judgements use the same criteria but assign them various importance.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 420-427